PROTECTION FOR CONTRACTORS IN CONSTRUCTION WORK CONTRACT DUE TO FORCE FORCE (Study in Banyuwangi Regency) - HARI PRANOTO (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
The thesis discusses legal protection in contruction work contracts at the stage of contract implementation when force majeure occurs. The problem in this research is how the legal protection for contraktors in contruktion work contracts due to force majeure. In writing this thesis the author uses empirical research methods, where data obtained from the field is analyzed to be used as a basis for discussion to minimize the risk of force najeure in construction work contract,especially on the part of service providers (contractors). By interviewing the executives or directors of CV who have experienced force majeure on the work contract of a project that they have implemented. The results of the study concluded that the employment contract arrangement of construction work is able to reduce the emergence of claims and prevent construction disputes, especially for the contractors. The concept of the approach with Law No. 2 of 2017 Concerning Construction Services and Presidential Regulation No. 16 of 2018 Concerning Government Procurement of Goods/Services. The implication of this researchin that the parties, both service users and service providers (contractors) should pay attention to the clauses governing force majeure contained in the contract. With the aim that all parties can solve the problem properly. Thus, the contract that concerned from the beginning can determine the choice of dispute resolution or problems that are considered best for the parties, especially the contractor